Laser and IPL Technology in Dermatology and Aesthetic Medicine - Raulin, Christian; Karsai, Syrus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
In this innovative textbook, renowned experts from the United States, Europe, and Asia present the most up-to-date information in the field of cutaneous laser surgery and intense pulsed light (IPL) technology. Technical and biophysical aspects of lasers and IPL devices are first discussed in depth to provide the reader with a sound understanding of basics. A series of richly illustrated chapters then carefully examine the numerous and diverse clinical applications of these techniques, highlighting both their potential and their limitations, including side-effects. In the concluding section, important miscellaneous topics are addressed, including cooling techniques, ethical and economic considerations, and laser safety. This book is designed to be of benefit to novice and experienced practitioners alike. In addition to providing expert guidance on the use of lasers and IPL devices in more than 80 clinical indications, it examines the role of new techniques such as laser lipolysis and fractional photothermolysis and includes sufficient information to assist the reader considering the purchase of laser or IPL equipment.
Benign Pigmented Lesions -- Benign Tumors and Organoid Nevi -- Dyschromias -- Inflammatory Dermatoses and Connective Tissue Diseases -- Wrinkles and Acne Scars -- Scars -- Unwanted Hair Growth -- Precancerous Conditions and Malignant Tumors -- Vascular Lesions -- Viral Infections -- Laser-assissted Lipolysis -- Cooling Techniques.
Keywords: Medicine; Dermatology; Family medicine; Surgery; Medicine & Public Health; Dermatology; Plastic Surgery; General Practice / Family Medicine